2011
DOI: 10.1007/s12094-011-0688-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results and prognostic factors of patients with cervical carcinoma treated with concurrent chemoradiotherapy

Abstract: Non-squamous histology and partial response were independent prognostic factors for overall survival and tumour size and partial response were independent prognostic variables for 5-year disease survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…These results are consistent with those of previous studies where tumor size [23,24] and non-squamous histological type [24-26] were identified as prognostic factors for the survival of FIGO stage IIB cervical cancer patients. Thus, the development of new treatment strategies for patients with known risk factors for survival is urgently needed.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with those of previous studies where tumor size [23,24] and non-squamous histological type [24-26] were identified as prognostic factors for the survival of FIGO stage IIB cervical cancer patients. Thus, the development of new treatment strategies for patients with known risk factors for survival is urgently needed.…”
Section: Discussionsupporting
confidence: 93%
“…Overall survival was measured from the date of the baseline MR scan to the date of death. Patients who were alive on the closeout date had their survival date censored to that date …”
Section: Methodsmentioning
confidence: 99%
“…Currently, it is also difficult to guide the prognosis evaluation of patients and stratify patients with persistent or recurrent disease into risk groups because of the heterogeneity of the associated factors and the radiosensitivity ( 12 ). However, most previous studies have reported these tumor prognostic factors with respect to survival outcomes after the completion of RT ( 7 , 13 ). Although the response after completion of RT is important, we hypothesized that tumor parameters, such as tumor size (TS), tumor volume (TV), and tumor volume reduction rate (TVRR), measured before the intracavitary radiotherapy (ICR), appear to have greater prognostic value ( 10 , 12 , 14 ).…”
Section: Introductionmentioning
confidence: 99%